2011
DOI: 10.1186/1471-2091-12-35
|View full text |Cite
|
Sign up to set email alerts
|

Amino-terminal extension present in the methionine aminopeptidase type 1c of Mycobacterium tuberculosis is indispensible for its activity

Abstract: BackgroundMethionine aminopeptidase (MetAP) is a ubiquitous enzyme in both prokaryotes and eukaryotes, which catalyzes co-translational removal of N-terminal methionine from elongating polypeptide chains during protein synthesis. It specifically removes the terminal methionine in all organisms, if the penultimate residue is non-bulky and uncharged. The MetAP action for exclusion of N-terminal methionine is mandatory in 50-70% of nascent proteins. Such an activity is required for proper sub cellular localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…As we confirmed mapB is essential for M. bovis growth, we wanted to examine whether knockout mutants are rescued by expression of MAP with modified activity. It was previously reported that MapB V18G and MapB W255L were highly defective in their methionine aminopeptidase activity as the substitution W255L affects the catalytic pocket, whereas V18G affects the N-terminus extension of the protein [17]. We first designed these two mutation sequences separately and also a mapB sequence containing both point mutations: mapB V18G , mapB W255L and mapB V18G;W255L .…”
Section: Resultsmentioning
confidence: 99%
“…As we confirmed mapB is essential for M. bovis growth, we wanted to examine whether knockout mutants are rescued by expression of MAP with modified activity. It was previously reported that MapB V18G and MapB W255L were highly defective in their methionine aminopeptidase activity as the substitution W255L affects the catalytic pocket, whereas V18G affects the N-terminus extension of the protein [17]. We first designed these two mutation sequences separately and also a mapB sequence containing both point mutations: mapB V18G , mapB W255L and mapB V18G;W255L .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the M. tuberculosis HBHA [23], native map-HBHA contains no initiation methionine at its N-terminus and that the first amino acid is thus an alanine residue. The cleavage of the initiation methionine is a post-translational common process in Mycobacteria [24,25]. The HR-MS/MS analyses also indicated that the amino-terminal alanine is acetylated.…”
Section: Resultsmentioning
confidence: 99%
“…However, many of them suffered from a poor activity against the pathogens. The bacterial secondary metabolite pyridomycin (43), produced by Streptomyces pyridomyceticus or Dactylosporangium fulvum [71], was found to be a direct inhibitor of InhA (Ki = 6.5 μM) and exhibited significant in vitro antimycobacterial activity against several Mtb strains, including H37Rv (MIC = 0.56 µg/mL), and INH-resistant clinical isolates [72].…”
Section: Nps Interfering With the Cell Wall And Fatty Acid Biosynthes...mentioning
confidence: 99%
“…3-deoxy-D-arabino-heptulosonate 7-phosphate synthase (DAH7Ps), shikimate kinase (SK), and acetohydroxyacid synthase (AHAS); hence, their fundamental role makes them attractive targets for the development of new antibiotics. MetAP removes the N-terminal methionine residue from newly synthesized proteins[43]. employed a pharmacophore-based virtual screening using synthetic and NP databases to identify new DAH7Ps inhibitors[46].…”
mentioning
confidence: 99%